A moda andrógina masculina dentro do movimento do glamour rock - Marcondes, Ivelise (2013)
In this study, we investigate on the fashion of young androgynous male, and these members or fans of bands that refer to glamour rock and take this style in their clothing. Shows up, so, so that these users a retelling of the movement of the 70's identifying characteristics of your clothing between the cities of Londrina and Apucarana. Therefore, in addition to the theoretical framework, we elaborated notes, questionnaires and interviews to obtain data that would allow developing a collection that serves only the physical and psychological needs of this audience highlighted.